Extracellular Vesicles as biomarkers of hepatic metastasis in pancreatic cancer patients - Saldanha, Inês de Almeida Mateus da Silva (2023)
Pancreatic cancer (PC) is currently considered a public health burden. Despite not being one of the main types of cancer nor one of the main causes of cancer-related deaths worldwide, the case-fatality rate extremely high. The diagnose of metastatic disease is usually performed by imagiological exams. However, these lack the sensitivity and specificity to detect earlier stages of the metastatic process, such as the pre metastatic niche (PMN) and micrometastasis. Interestingly, extracellular vesicles (EVs) have been described to be involved in the formation of the PMN by transporting molecules from their secreting cells (both tumor and tumor-associated) to biofluids, and thus represent an accessible source of biomarkers for disease diagnosis and monitoring, and as prognostic and predictive tools. Hence, the main purpose of this Master Thesis is to evaluate whether circulating EVs can early detect the presence of hepatic metastatic disease in PC patients. For this purpose, we have developed an animal model with PC liver metastasis, to collect plasma and both tumor and stromal cells from the liver. Cells were cultured and derived EVs were isolated. The detailed characterization of EVs protein composition was performed by mass spectrometry. The results showed several proteins to be upregulated in the plasma EVs of metastatic PC mice, as well as in the tumor or stroma derived EVs, when compared to the plasma and stroma derived EVs of healthy mice, highlighting the potential of EVs present in the plasma to be used as PC biomarkers. Hence, further statistical analysis and literature reviewing were performed to select a tumor (Rab11b) and a stromal (SERT) marker. Although both have been described to be directly or indirectly involved in biological processes related with tumor progression, some other studies have associated their mRNA levels with a good prognosis. Hence, we decided to pursue with both these proteins to investigate whether their expression levels in human plasma derived EVs could be associated with hepatic metastasis. Our results showed that, in human plasma samples, a higher percentage of EVs Rab11b+ was linked to longer metastasis-free survival, contrasting the findings in our PC mouse model. Furthermore, EVs SERT+ levels showed varied associations with survival over different timepoints, emphasizing the dynamic nature of the stromal context. A higher tumor-stroma ratio (TSR) at 6 to 8 months post-diagnosis indicated prolonged metastasisfree survival, highlighting the stroma's pro-tumoral role. Additional particle and fluorescence intensity analyses yielded no major significant distinctions.